Regioselective Synthesis of Substituted Tetrahydrofurans through Prins Cyclization - Zhao, Li-Ming; Dou, Fei; Sun, Rui; Zhang, Ai-Li (Synlett, 2014)
The synthesis of functionalized tetrahydrofurans was accomplished through the TfOH-catalyzed Prins cyclization. The reaction proceeded regioselectively at the internal alkene carbon in the presence of catalytic amounts of TfOH to afford the five-membered ring, rather than the typical six-membered ring. Another attractive feature of this protocol is the metal catalyst-free characteristic of the cyclization process.
Keywords: alcohols; aldehydes; furans; cyclization; regioselectivity